2015
DOI: 10.1111/ajgw.12121
|View full text |Cite
|
Sign up to set email alerts
|

Multicultivar and multivariate study of the natural variation for grapevine bunch compactness

Abstract: Background and Aims Grapevine bunch compactness is an important trait with impact on fruit quality, mainly affecting the susceptibility to bunch rot. Many and different variables have been reported to have a significant influence on the variation of bunch compactness in particular cultivars, but little is known about the role of such variables in a wider framework. The aim of this work was to identify and weight the features responsible for the natural variation in bunch compactness in a large and diverse grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 55 publications
5
61
0
Order By: Relevance
“…1). As previously reported in different intergenotypic works (Leão et al 2010(Leão et al , 2011Khadivi-Khub et al 2014;Tello et al 2015), the highest absolute correlations were obtained between traits of the same category (i.e. leaf, cluster and berry traits, Table 1).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…1). As previously reported in different intergenotypic works (Leão et al 2010(Leão et al , 2011Khadivi-Khub et al 2014;Tello et al 2015), the highest absolute correlations were obtained between traits of the same category (i.e. leaf, cluster and berry traits, Table 1).…”
Section: Resultssupporting
confidence: 83%
“…Interestingly, seed number (BE_SB) did not correlate significantly with berry dimension variables (BE_We, BE_Wi) or its value of significant correlation was low (BE_Le). It is generally accepted that berry dimensions are directly affected by seed number at a intragenotypic level (Walker et al 2005), but it is not that obvious at an intergenotypic level Tello et al 2015). In this regard, Doligez et al (2013) have indicated the lack of colocalization between QTLs for berry and seed traits, suggesting that the genetic control of both traits may be partly dissociated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, cluster selection is becoming a common practice at some wineries for selecting high quality fruits to produce premium wines . In this light, winemakers usually reject highly compact clusters, which are considered of lower quality . Cluster size, shape and compactness are routinely evaluated by visual methods, like those proposed by the International Organisation of Vine and Wine (O.I.V.)…”
Section: Introductionmentioning
confidence: 99%
“…Each ramification comprises a highly variable number of berries, whose size and shape also vary widely . This singular structure means two different volumes can be considered in the cluster: the actual (or solid) and the morphological (or apparent) one, and cluster compactness is determined by the difference between them . The actual volume of the cluster is mainly composed of the volume of the berries (the volume of the rachis – or stem – is insignificant), whereas the morphological one is also defined by the way that this solid volume is arranged three‐dimensionally .…”
Section: Introductionmentioning
confidence: 99%